The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/plants11030286
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and Mowing Affect the Carbon-to-Nitrogen Ratio of Plants by Changing the Soil Available Nitrogen Content and Soil Moisture on the Meadow Steppe, China

Abstract: Common grassland management practices affect plant and soil element stoichiometry, but the primary environmental factors driving variation in plant C/N ratios for different species in different types of grassland management remain poorly understood. We examined the three dominant C/N stoichiometric responses of plants to different land uses (moderate grazing and mowing) in the temperate meadow steppe of northern China. Our results showed that the responses of the C/N ratio of dominant plants differed according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…As for the tunnel water, no temperature was recorded in the winter due to the lack of pumping into tunnel, and the lowest recorded temperature was 21 C° in May, with the start o f the irrigation season. Studies indicate [30], [31] that the more as the temperature rises, the ratio of carbon to nitrogen (C: N) in surface water increases due to the decomposition of organic matter these approved by our Previous research by [19] showed an increase in the ratio of C: N in the samples of the months of July and September in lake water 23, 22.5, respectively. Along with temperatures of 31.5 and 28.9 C°for the year 2019, respectively, due to the decomposition of plant residues by the existing bacteria, and this is what we will notice later in pseudomonas counts.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As for the tunnel water, no temperature was recorded in the winter due to the lack of pumping into tunnel, and the lowest recorded temperature was 21 C° in May, with the start o f the irrigation season. Studies indicate [30], [31] that the more as the temperature rises, the ratio of carbon to nitrogen (C: N) in surface water increases due to the decomposition of organic matter these approved by our Previous research by [19] showed an increase in the ratio of C: N in the samples of the months of July and September in lake water 23, 22.5, respectively. Along with temperatures of 31.5 and 28.9 C°for the year 2019, respectively, due to the decomposition of plant residues by the existing bacteria, and this is what we will notice later in pseudomonas counts.…”
Section: Resultsmentioning
confidence: 89%
“…16 th Tishreen Dam Lake site: The Pseudomonas aeruginosa counts decreased in the 16 Tishreen dam lake water to the low values of 1000 cfu/100 mL in August due to the stratification of the lake and the redistribution of Pseudomonas between the surface and deep layers of the lake water and then its release again from the sediments in the deep and dark waters that stimulate the growth of bacteria, as we will notice in the tunnel water. The highest values were recorded in the lake water in autumn, as the counts increased to 19000 cfu/100 mL in October 2019 with a turbidity rise of 13.2 NTU, and the counts recorded in October 13000 cfu/100 mL associated with a turbidity of 3.88 NTU, a decrease in the lake level and decomposition of plant residues, causing an increase in the C/N ratio [31]. On the other hand, the lowest concentration of 420 cfu/100mL recorded in the lake water in May 2019, associated with a relatively low turbidity of 2.27 NTU and the lowest pH value of 7.75.…”
Section: Pseudomonas Aeruginosa Changesmentioning
confidence: 90%
“…In the experimental field, Leymus chinensis (Trin.) Tzvel., Bromus inermis Leyss., and Potentilla bifurca L. represent the dominant plant species [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The high input of exogenous carbon is conducive to the growth of roots, which changes the quantity and chemical composition of root exudates, affects the functional groups and quantity of soil organisms, and significantly increases the content of soil EOC (Sun et al, 2013). Under sustainable conservation tillage, Due to the continuous decomposition of straw mulching and the input of carbon into the soil, the content of soil carbon components increased continuously (Wang et al, 2022).…”
Section: Effects Of Sustainable Conservation Tillage On Soil Carbon C...mentioning
confidence: 99%